Neer Type II Distal End Clavicular Fracture: Outcome with Clavicular Hook Plate Fixation - Panthi, Sagar (Europasian Journal of Medical Sciences, 2020)
Background: Distal end clavicular fractures are rare type of injuries seen in adult population. These fractures are unstable because of various deforming forces. Clavicular hook plate aligns the clavicle along with ligaments. The aim of this study is to observe the outcome of displaced distal end clavicular fracture managed with hook plate fixation. Methods: Twenty five patients with displaced distal end clavicular fractures (Neer type II) were evaluated retrospectively from November 2018 to September 2020. Functional outcome were assessed via Constant and Murley score at one year final follow-up. Results: Sixty percentage of patient had excellent outcome, 32% of patient had good outcome and 8% of patient had fair outcome at final follow-up. Mean Constant and Murley score was 86. Four patients developed subacromial osteolysis which resolved at final followup. One patient had extra-articular ossification whereas none of the patient developed non-union and AC joint arthrosis. Conclusion: Clavicular hook plate provides stable fixation of distal end clavicular fracture with few complications and is cost-effective.